Latin American women dramatists : theater, texts, and theories - Larson, Catherine, 1950-; Vargas, Margarita, 1956- (Indiana University Press, 1998)
"The book highlights the many possibilities of the innovative work of these dramatists, and this will, it is to be hoped, help the editors to achieve one of their other key goals: productions of the plays in English."--Times Literary Supplement"This thoughtfully crafted book with its insightful and informative studies elucidates an overlooked, essential component of the Latin American literary canon."--ChoiceContributors discuss 15 works of Latin-American playwrights, delineate the artistic lives of